2021
DOI: 10.1136/bcr-2020-239611
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and severe biphasic disturbance of calcium homeostasis secondary to COVID-19 infection

Abstract: We report a case of severe hypercalcaemia secondary to rhabdomyolysis in a woman with COVID-19 (SARS CoV-2) infection. The patient presented with myalgia and anuria with an acute kidney injury requiring haemodialysis. Creatine kinase peaked at 760 000 IU/L. A biphasic calcaemic response was observed with initial severe hypocalcaemia followed by severe, symptomatic hypercalcaemia, persistent despite haemodialysis. Control of the calcium levels was achieved by continuous haemofiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Viral infection is a recognized cause of rhabdomyolysis which often initially presents with myalgias. Similar cases of rhabdomyolysis associated with COVID-19 infection have been reported in the literature beginning in the early months of the pandemic [4][5][6][7][8][9][10][11][12][13]. Our report demonstrates a case of rhabdomyolysis with an extremely high CK value that was treated with a high flow rate of IV fluids and resolved completely with no residual kidney disease and no need for hemodialysis during treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Viral infection is a recognized cause of rhabdomyolysis which often initially presents with myalgias. Similar cases of rhabdomyolysis associated with COVID-19 infection have been reported in the literature beginning in the early months of the pandemic [4][5][6][7][8][9][10][11][12][13]. Our report demonstrates a case of rhabdomyolysis with an extremely high CK value that was treated with a high flow rate of IV fluids and resolved completely with no residual kidney disease and no need for hemodialysis during treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Viral infection is a recognized cause of rhabdomyolysis, which often initially presents with myalgias, as many viruses also do without concurrent rhabdomyolysis [1]. Numerous case studies have specifically reported associations between COVID-19 infection and rhabdomyolysis [4][5][6][7][8][9][10][11][12][13][14]. Thus, it is important to monitor COVID-19 patients with appropriate physical exams and labs in order to diagnose rhabdomyolysis early, initiate treatment, and mitigate downstream effects of proteinemia and myoglobinuria, such as acute kidney injury [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hypercalcemia has recently been linked to COVID-19, but the exact mechanism of this association remains poorly understood [ 13 ]. Although most reported cases have occurred in settings of immobilization or rhabdomyolysis due to critical illness, hypercalcemia after COVID-19 has not been commonly observed in cases of malignancy [ 14 , 15 ]. Symptomatic hypercalcemia has been recognized with both multiple myeloma and immobility in patients with COVID-19 [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hypercalcemia in hospitalized patients with COVID-19 is rare (exact frequency unknown), but it is associated with poorer prognosis . Potential mechanisms include rhabdomyolysis, immobilization, and post–COVID-19 granulomatous disease . Fourteen children with epilepsy who were following a ketogenic diet were reported to develop hypercalcemia .…”
Section: Observations and Discussionmentioning
confidence: 99%
“…32 Potential mechanisms include rhabdomyolysis, immobilization, and post-COVID-19 granulomatous disease. [32][33][34][35][36] Fourteen children with epilepsy who were following a ketogenic diet were reported to develop hypercalcemia. 37 The mechanism, while not fully delineated, may be due to low bone formation.…”
Section: Normal Regulation Of Calciummentioning
confidence: 99%